A history of the bible: the book and its faiths - Salvesen, A (Liverpool University Press, 2022)

(untitled)
John Barton, A History of the Bible: The Book and Its Faiths. Allen Lane, London, 2019. xvii, 613pp, £25.00. ISBN 978 0 24100 391 6.